2018
DOI: 10.1002/anie.201800453
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electronic Structure of Boron‐Graphdiyne with an sp‐Hybridized Carbon Skeleton and Its Application in Sodium Storage

Abstract: Boron-graphdiyne (BGDY), which has a unique π-conjugated structure comprising an sp-hybridized carbon skeleton and evenlydistributed boron heteroatoms in a well-organized 2D molecular plane, is prepared through a bottom-up synthetic strategy. Excellent conductivity, a relatively low band gap and a packing mode of the planar BGDY are observed. Notably, the unusual bonding environment of the all sp-carbon framework and the electron-deficient boron centers generates affinity to metal atoms, and thus provides extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 29 publications
6
120
0
1
Order By: Relevance
“…In this structure, only three different types of atoms exist; B atoms and C atoms connected with either B or C atoms. In accordance with the original experimental work by Wang et al 36 , C atoms connected with B and C atoms are distinguished with 1C and C3 terms, respectively. In the energy minimized structure, the B-1C, 1C-C3 and C3-C3 bond lengths were measured to be 1.512 Å, 1.235 Å and 1.345 Å, respectively.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…In this structure, only three different types of atoms exist; B atoms and C atoms connected with either B or C atoms. In accordance with the original experimental work by Wang et al 36 , C atoms connected with B and C atoms are distinguished with 1C and C3 terms, respectively. In the energy minimized structure, the B-1C, 1C-C3 and C3-C3 bond lengths were measured to be 1.512 Å, 1.235 Å and 1.345 Å, respectively.…”
Section: Resultssupporting
confidence: 87%
“…6 illustrates the band structure along the high symmetry directions, total and partial EDOS of C 12 B 2 monolayer predicted by PBE method. Our results indicate that the unstrained C 12 B 2 monolayer is a direct band-gap semiconductor at Γ point, which is in a good agreement with the theoretical predictions by Wang et al 36 . The band-gap of freestanding and stress-free C 12 B 2 within the PBE functional was measured to be 0.48…”
Section: Electronic and Optical Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…[33][34][35][36][37][38] These materials can exist as heterostructures consisting of several layered 2D materials 33,[39][40][41] such as graphene/phosphorene, graphene/InSe, and boron nitride/phosphorene or 2D layers consisting of atoms of different elements. [42][43][44] It has been demonstrated that heterostructures formed by 2D materials, which are unstable in strand ambient conditions, such as phosphorene, and 2D materials, which are stable, such as graphene, are characterized by improved stabilities. 37,38,45,46 Very recently, a stable allotrope of phosphorus carbide (PC), a 2D monolayer consisting of carbon and phosphorus atoms, has been discovered.…”
Section: Introductionmentioning
confidence: 99%